2021
DOI: 10.1093/conphys/coab070
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a mouse Doppler echocardiograph system for assessing cardiac function and thermal performance in a juvenile salmonid

Abstract: Measures of cardiac performance are pertinent to the study of thermal physiology and exercise in teleosts, particularly as they pertain to migration success. Increased heart rate, stroke volume and cardiac output have previously been linked to improved swimming performance and increased upper thermal tolerance in anadromous salmonids. To assess thermal performance in fishes, it has become commonplace to measure the response of maximum heart rate to warming using electrocardiograms. However, electrocardiograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In comparison, the lower heart rate cherry salmon had longer ventricular diastole, and the event of ventricular filling of blood occurred before atrial contraction began; however, no biphasic inflow waveform was observed in masu salmon, even though the time duration from ventricular ejection to the onset of atrioventricular inflow increased. However, since juvenile Atlantic salmon of 15 g body weight showed biphasic waveforms [95], it is possible that our data of pulsed-wave Doppler echocardiography are O. masou -specific. Elastic reaction forces, muscle contraction, and differences in chamber size between the atria and ventricles have been considered as candidates for the driving forces of ventricular filling, but they have not been sufficiently understood yet [96, 97].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the lower heart rate cherry salmon had longer ventricular diastole, and the event of ventricular filling of blood occurred before atrial contraction began; however, no biphasic inflow waveform was observed in masu salmon, even though the time duration from ventricular ejection to the onset of atrioventricular inflow increased. However, since juvenile Atlantic salmon of 15 g body weight showed biphasic waveforms [95], it is possible that our data of pulsed-wave Doppler echocardiography are O. masou -specific. Elastic reaction forces, muscle contraction, and differences in chamber size between the atria and ventricles have been considered as candidates for the driving forces of ventricular filling, but they have not been sufficiently understood yet [96, 97].…”
Section: Discussionmentioning
confidence: 99%
“…We determined cardiorespiratory thresholds for thermal performance in the two developmental treatments by measuring the response of pharmacologically stimulated maximum heart rate ( f Hmax ) to acute warming using noninvasive Doppler echocardiography in anaesthetized juveniles, according to Muir et al (2021b) . In these thermal performance trials, temperature was increased at a rate of 10°C h −1 until the onset of cardiac arrythmias, starting from the fish's respective rearing temperatures (11°C for +0-fish and 15°C for +4-fish; Muir et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…No biphasic inflow waveform was observed, in masu salmon, even though the time duration from ventricular ejection to the onset of atrioventricular inflow increased. Further, since juvenile Atlantic salmon of 15 g body weight showed biphasic waveforms [87], it is possible that our data derived from pulsed-wave Doppler echocardiography are species specific. Elastic reaction forces, muscle contraction, and differences in chamber size between the atria and ventricles have been considered as candidates for the driving forces of ventricular filling, but are not yet sufficiently understood [88,89].…”
Section: Differing Ventricular Diastolic Hemodynamicsmentioning
confidence: 99%